Brief Assessment of Parental Perception (BAPP): Development and validation of a new measure for assessing paediatric outcomes after bilateral cochlear implantation. (1st November 2016) - Samuel, V.; Gamble, C.; Cullington, H.; Bathgate, F.; Bennett, E.; Coop, N.; Cropper, J.; Emond, A.; Kentish, R.; Edwards, L.
Abstract: Objective : In contrast to previous clinical practice, current guidelines recommend bilateral cochlear implantation in children, resulting in a cohort of children who initially received one implant, but have subsequently had a second, contralateral implant. This study aimed to explore satisfaction and quality of life in children implanted simultaneously or sequentially. Design : A novel measure of satisfaction and quality of life following paediatric bilateral cochlear implantation (the Brief Assessment of Parental Perception; BAPP) was developed and preliminary validation undertaken as part of a large, national project of bilateral implantation. Children's parents completed the measure yearly for up to three years following implantation. Study sample : Children from 14 UK implant centres were recruited into the study; data were available for 410 children one year post-implantation. Results : The BAPP was found to have good face and convergent validity, and internal consistency. Results indicated very high levels of satisfaction with the devices, and improvements in quality of life. However there was evidence that children implanted sequentially were less willing to wear their second implant in the first two years than those children receiving simultaneous implants. Conclusion : Simultaneous and sequential cochlear implants have a positive impact on the quality of life of deaf children.